Pengaruh Kualitas Produk, Persepsi Harga dan Atmosphere terhadap Keputusan Pembelian Di Feel Matcha Kemang - Endryanti, Endryanti; Talumantak, Ricky (Peneliti.net, 2025)
This research aims to determine and analyze the influence of product quality, price perception and atmosphere on purchasing decisions at Feel Matcha Kemang. This research uses quantitative methods, namely methods that take large amounts of data with the aim of testing hypotheses. Primary data were gathered by questionnaires, and SPSS version 27 was utilized to process the data in order to create a research population comprising all Feel Matcha Kemang customers. Using the Accidental Sampling Technique, 100 respondents made up the sample. A multiple linear regression model method is employed in this study. So the results of this research state that product quality has a significant effect on purchasing decisions, while the Atmosphere variable does have a significant effect on purchasing decisions. According to the research results, it can be concluded that product quality, price perception and atmosphere simultaneously have a significant influence on purchasing decisions at Feel Matcha Kemang.